Considerations on the applicability of OECD TG 453 to whole food/feed testing. (31st July 2013) - ,
Abstract: Upon request from the European Commission, the European Food Safety Authority prepared a scientific report that would aid the future establishment of protocols for chronic toxicity and/or carcinogenicity studies in rodents with whole food/feed. This scientific report provides a commentary on OECD TG 453 with considerations on its applicability to support the safety assessment of long term consumption of a given food with respect to its chronic toxicity or carcinogenicity potential. The decision to conduct chronic toxicity and/or carcinogenicity studies with whole food/feed should be taken on a case‐by case basis. It should be based on the evaluation of all the available information on the whole food/feed resulting from compositional analyses and any other available nutritional and toxicological studies. The conduct of the study and its reporting should be in line with good laboratory practice standards. Preparation of appropriate test diets is a key element of the experiment with respect to characterisation of the starting material and of the diet, level of inclusion of whole food/feed, nutritional balance, processing and storage. Statistical considerations are discussed to assist in estimating the number of animals necessary to obtain a suitable sample size capable of detecting biologically relevant effects with a pre‐specified power and significance level. A comprehensive set of endpoints as set out in the OECD TG 453 should be measured during and at the end of the study, as appropriate. The collection of data and reporting should ensure a thorough biological and statistical evaluation. Recommendations on the relevant issues to be considered when designing chronic toxicity and/or carcinogenicity studies in rodents with whole food/feed are provided throughout the report and summarised in the conclusions.